The in Vivo and in Vitro Effect of Antihistamines on Platelet Aggregation - Ungaro, Peter C.; Beck, Thomas M.; McCaa, William M.; Hershgold, Edward J. (Thrombosis and Haemostasis, 1973)
The effect of antihistamines on platelet aggregation was studied by examining the platelet rich plasma of subjects taking three representative classes of these drugs, as well as by studying the effect of direct addition of antihistamine to platelet rich plasma. Inhibition of aggregation by in vitro addition was obtained only with drug concentrations much greater than would usually be found in vivo. Platelet aggregation was unimpaired in normal volunteers taking standard doses of antihistamines.